PERAN DAN PENGGUNAAN BAHASA INDONESIA DALAM PENGAJARAN DAN PEMBELAJARAN BAHASA INGGRIS SEBAGAI BAHASA ASING - Zainuddin Zainuddin (Universitas Islam Zainul Hasan Genggong, 2025)
Most students and even English as a Foreign Language (EFL) teachers still struggle to speak with correct grammar and fluency due to a lack of mastery and understanding of the Indonesian language. This research was conducted to investigate how the Indonesian language can assist EFL teachers and students in improving their English skills and comprehension. The data were analyzed using the Miles and Huberman framework, which includes data reduction, data presentation, and conclusion drawing and verification. The findings show both positive and negative perceptions from teachers regarding the role of Indonesian in EFL teaching and learning. The second finding reveals five roles of Indonesian: as Functional Equivalence, Competence Indicator, Linguistic Mediator, Communicative Language Paradigm, and Situational Language Use. The third finding explores the aspects in which Indonesian plays a role in assisting EFL teaching and learning, such as the aspects of Linguistic Items, Semantics, and Pragmatics. The study also found three additional findings: Linguistic Competence vs. Linguistic Cognition, Culture-Based Language Behavior, and Interest in the First Language.